A numerical modelling study of the interannual variability in the Indian Ocean - BEHERA , S. K.; SALVEKAR, P. S. (MAUSAM, 1995)
A simple reductA1 gravity wind-driven ocean circulation model is used to study the interannual variability in the upper layer of the Indian Ocean (24°S-23°N and 3S°E-IIS0E). The monthly mean wind stress for the period 1977-1986 are used as a forcing in the model. The model reproduces most of the observed features of the annual cycle of the upper layer circulation in the Indian Ocean when was forced with the ten-year average monthly mean wind. The circulation features and the model upper layer thickness show considerable interannual variability in most part of the basin; in particular, the Somali Current, the basin wide southern hemisphere gyre, the Equatorial Currents and the gyres in the Bay of Bengal. Six consecutive years starting from 1978 to 1983 which include two bad monsoon years of 1979 and 1982 are chosen to study the interannual variability. February circulation field shows stronger Equatorial Counter Currents in bad monsoon years, whereas. the cunents north of Madagascar flowing up to the African coast are found to be stronger in good monsoon years. The southward return flow from the Southern Gyre in August is strong and more to southern latitudes in the bad monsoon years. The flow circulated eastward to form another eddy east of Southern Gyre. The basin wide gyre of the southern hemisphere (SH) shows less variability in two consecutive normal years than in contrasting years.